TINJAUAN ETNOSEJARAH DALAM PENELITIAN ARKEOLOGI DI KABUPATEN BIAK NUMFOR - Wasita (BRIN, 2000)
Archaeological research at BN which utilizes ethno-history as one of its methods, can in fact provide important information regarding the history of the site. This information can assist researchers in determining the periodicity of the site. Sorkdi site are prehistoric, but if you pay attention to the results of the study of oral history and old texts, the conclusion points to sites of prehistoric traditions (farming traditions). Using the same method (ethnohistoric), it is pointed out that the Sowek site and Wow Sikiki Cave are also sites of prehistoric traditions. The Sowek site is similar in case to Sorkdi, while the Wow Sakiki Cave is suspected of being a prehistoric tradition site because there are no findings indicating the origin of the neolithic period. Meanwhile, if you pay attention to the old text which states that a korwar statue (perhaps a painting of a korwar statue, a statue that is always created by followers of the Koreri movement), then this clarifies the periodization of Wow Sakiki Cave as a site of prehistoric traditions.